Mixed Methods Systematic Review : Kejadian Cabin Fever Selama Pembatasan Sosial Saat Penyebaran Penyakit Sars, Mers Dan Covid-19 - Michelle Christo; Lintang Dian Saraswati; Ari Udiyono; Dwi Sutiningsih (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: SARS, MERS and Covid-19 are the most dangerous viruses among the Human Coronavirus (HCoV). The spreading of those diseases could cause cabin fever due to social restrictions as the control and prevention efforts. This study aims to map the impact of cabin fever during HCoV pandemic by the characteristic population and its causing factors.Methods: A mixed method systematic review was conducted in five databases and its keywords were determined using MeSH (Medical Subject Headings). All articles were assessed after passed the last process (included). There are 11 articles included and 3 of them rated as strong quality. The findings were grouped into themes related to population characteristics and causative factors.Result: The result shows among 4 themes of population characteristic, college student shows more than five symptoms of cabin fever. Out of all the causing factors, quarantine and social distancing shows more than five symptoms of cabin fever.Conclusion: This review proves that cabin fever can occurs during the outbreak, epidemics and pandemics so, psychological treatment in the communities is needed during the spreading of the viruses. The treatment must be right because the symptoms of cabin fever differ according to population and the causes.